A Topological Stitching Strategy for Biocompatible Wet Adhesion Using Mussel‐Inspired Polyurethane. Issue 18 (31st August 2021) - Chen, Buyun; Lei, Kun; Zhu, Dandan; Yang, Chongchong; Sun, Chengyuan; Xiao, Wei; Zheng, Zhen; Wang, Xinling
Abstract: The biomedical and surgical applications of hydrogels demand effective methods to adhere hydrogels to diverse substrates including living tissues. Here a mussel mimetic polyurethane as topological suture material for tough adhesion of hydrogels by introducing catechol moieties into polymer chains is presented. Solution of the stitching polyurethane can be injected onto the surface of a hydrogel, followed by diffusing spontaneously into the hydrogel, then get triggered by oxidant for in situ gelation. Oxidative cross‐linkage of catechol‐modified polyurethane after penetration into hydrogels or living tissues can establish enough covalently entangled networks to afford desired adhesion strength. The mussel mimetic polyurethane demonstrates excellent adhesion strength of hydrogels to versatile substrates including inorganics, polymers, and biomaterials, with no requirements for specific functional groups or chemical modification. The adhesion energy achieved by the topological stitching strategy can reach up to 350 J m −2 . Moreover, the stitching polymer shows potential for debonding under the catalysis of elastase. This work will possibly become a promising strategy candidate for adhesion in wet environments. Abstract : A robust adhesion is established using mussel‐mimetic polyurethane as topological suture. The catechol containing stitching polyurethane can integrate hydrogel to diverse substrates via covalent entanglement and catechol chemistry, with a satisfying adhesion strength up to 350 J m −2 . Moreover, the stitching polyurethane demonstrates potential for elastase‐catalyzed interfacial debonding and biomedical use.